Influence of proliferation signal inhibitors on vascular endothelial growth factor production in heart transplant recipients – preliminary report - Kamieńska, Natalia; Zakliczyński, Michał; Kasperska-Zając, Alicja; Szewczyk, Marta; Trybunia-Orzeszek, Dominika; Nożyński, Jerzy; Pijet, Marta; Hrapkowicz, Tomasz; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Proliferation signal inhibitors (PSI) are especially beneficial for heart transplant recipients, but are rarely used due to frequent side effects. As they may be caused by vascular endothelial growth factor (VEGF), we performed a prospective cross-sectional pilot study to assess the influence of PSI and/or calcineurin inhibitors (CNI) presence in immunosuppressive protocols of heart transplant recipients on VEGF secretion. All electively screened heart transplant recipients willing to participate were enrolled in the study. The preliminary report was based on the results of the first 89 serum samples. The study group (n = 84) consisted of the PSI group (n = 14) further divided into the PSI + CNI subgroup (n = 10) and PSIw/oCNI subgroup (n = 4) based on concomitant CNI use, and the CNIw/oPSI group (n = 70) receiving CNI without PSI. The control group (n = 5) consisted of patients not requiring immunosuppression. VEGF was present in serum of 70 (83%) study group patients: median (range) 18 (0-316) pg/mL, mean 35 ± 57 pg/mL; in 13 (93%) PSI group patients: 22 (0-110) pg/mL, 28 ± 28 pg/mL, with 19 (8-20) pg/mL, 16 ± 6 pg/mL in the PSI+CNI subgroup, and 29 (0-110) pg/mL, 32 ± 32 pg/mL in the PSIw/oCNI subgroup. In the CNIw/oPSI group VEGF was present in 57 (81%) patients: 16 (0-316) pg/mL, 37 ± 62 pg/mL, and in the control group in 3 (60%) patients: 4 (0-110) pg/mL, 32 ± 48 pg/mL. None of the differences observed between any compared groups and/or subgroups was significant (χ2 and Mann-Whitney U test). In conclusion, differences of VEGF concentration observed among groups imply the influence of PSI and CNI on VEGF production, but further studies involving higher numbers of participants are needed to prove it.